2015
DOI: 10.1097/icl.0000000000000074
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and Intrasession Reproducibility Obtained by the Sirius Anterior Segment Analysis System

Abstract: The Sirius Scheimpflug system has a very high repeatability and intrasessional reproducibility when measuring the ACD, ACA, anterior curvature parameters, and the thinnest corneal location. Thus, it can be used with confidence in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 19 publications
5
28
2
Order By: Relevance
“…Accordingly, S w was below 1.22°for all temporal IA measurements. This is consistent with intra-observer variability reported previously for IA measured using Scheimpflug imaging [8,17]. Bosem et al [17] found mean intra-observer variability in IA measurement of 1.81°in a sample of healthy eyes, including open and narrow angles, using a Scheimpflug photography-based system.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Accordingly, S w was below 1.22°for all temporal IA measurements. This is consistent with intra-observer variability reported previously for IA measured using Scheimpflug imaging [8,17]. Bosem et al [17] found mean intra-observer variability in IA measurement of 1.81°in a sample of healthy eyes, including open and narrow angles, using a Scheimpflug photography-based system.…”
Section: Discussionsupporting
confidence: 85%
“…Some studies have assessed the repeatability of various anterior segment measurements provided by the same Scheimpflug imaging-based system as that used in the current study [6][7][8][9][10], with most reporting high levels of consistency [10][11][12][13][14]. However, few works have studied the repeatability of IA measurements [8], and to date, there is no study validating the consistency of measurements provided by the glaucoma mode of the Scheimpflug imagingbased system used in our series. In the current study, we evaluated the repeatability of IA measurements provided by this glaucoma mode, which analyzes the angle at different nasal and temporal meridians (−30°to 30°).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The Scheimpflug placido imaging technology (Sirius) is a relatively new advancement that has been reported to be highly reproducible and repeatable [27,32,33]. To the best of our knowledge, this is the first study that investigated the characterization of anterior segment parameters of keratoconus eyes using the Scheimpflug-placido Sirius topographer in a Southern Egyptian population.…”
Section: Discussionmentioning
confidence: 99%
“…All the other measurements for internal structures (posterior corneal curvature, anterior lens surface, and iris) are derived solely from Scheimpflug data. Previous studies have reported that the system's pachymetric and shape measurements (curvature, eccentricity, elevation) have good repeatability [23,27]. Measurements were performed by a single experienced examiner (EM).…”
Section: Methodsmentioning
confidence: 99%